Audios y videos digitales: una herramienta tic para fortalecer la cultura ambiental (2020)
The present research work consists in creating an educational proposal, where primary school teachers implement the use of digital videos and audios to strengthen the environmental culture. Mainly, this idea arises from the environmental problem that surrounds the INSTITUCIÓN EDUCATIVA PRIMERO DE MAYO, starting from their own spaces, both internal and external and from the social context where it is located. The contribution of several authors was taken into account in order to give solidity to this proposal, such as: Boff (1995) in his book “Ecology, cry of the earth”, Severiche (2016) and his contributions related to ecological culture, Panayotou (1994) with his thesis "Ecology environment and development", Monteagudo (2007) who expresses the importance of video as a tool for teaching; and others. The previous authors with their postulates support the proposal of this work which aims to strengthen the environmental culture through videos and digital audios. This research work is oriented towards an experiential introspective approach, a socio-critical paradigm, a qualitative design and a participatory action research design. The research group implemented the proposal to 10 primary school teachers, carrying out various activities, including watching and listening to audios and videos in relation to the environment and their care, which were previously selected. Finally, to verify the viability of the proposal, techniques and instruments were applied: the survey, using a questionnaire as an instrument, interview with a question guide and focus group with the focus group guide. The application of these, the evaluative evaluation of the results and highlight the relevance of the audios and videos, since the environmental culture in teachers can be strengthened, because after watching the videos and listening to the audios, a space was created where Their experience revealed the new actions to be taken into account to strengthen the environmental culture in the school, where they would include the entire educational community.